Do banks price their informational monopoly? - Hale, Galina; Santos, João A.C. (Journal of Financial Economics, 2009)
Theory suggests that banks’ private information lets them hold up borrowers for higher interest rates. Since new information about a firm is revealed at the time of its bond IPO, it follows that banks will be forced to adjust their loan interest rates downwards after firms undertake their bond IPO. We test this hypothesis and find that firms are able to borrow at lower interest rates after their bond IPO. Importantly, firms that get their first credit rating at the time of their bond IPO benefit from larger interest rate savings than those that already had a credit rating. These findings provide support for the hypothesis that banks price their informational monopoly. We also find that it is costly for firms to enter the public bond market.